2020
DOI: 10.1080/16066359.2020.1751130
|View full text |Cite
|
Sign up to set email alerts
|

A call for replications of addiction research: which studies should we replicate and what constitutes a ‘successful’ replication?

Abstract: A call for replications of addiction research: which studies should we replicate and what constitutes a 'successful' replication? Addiction Research & Theory

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…Accordingly, we aimed to understand how effectively gambling researchers are currently preregistering their studies by comparing their preregistration specificity scores (according to Bakker et al's [2020] scoring protocol) with the specificity scores recorded for the randomly selected, cross-disciplinary preregistrations in Bakker and colleagues' study. As the discussion of open science principles and practices in the gambling field has been limited until recently (Blaszczynski & Gainsbury, 2019;Heirene, 2020;Heirene & Gainsbury, 2020;LaPlante, 2019;Louderback et al, 2020;Wohl et al, 2019), we hypothesized that preregistrations of gambling-focused research studies would have lower specificity levels (i.e., have lower scores on the RDoF scoring protocol) than the cross-disciplinary sample.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we aimed to understand how effectively gambling researchers are currently preregistering their studies by comparing their preregistration specificity scores (according to Bakker et al's [2020] scoring protocol) with the specificity scores recorded for the randomly selected, cross-disciplinary preregistrations in Bakker and colleagues' study. As the discussion of open science principles and practices in the gambling field has been limited until recently (Blaszczynski & Gainsbury, 2019;Heirene, 2020;Heirene & Gainsbury, 2020;LaPlante, 2019;Louderback et al, 2020;Wohl et al, 2019), we hypothesized that preregistrations of gambling-focused research studies would have lower specificity levels (i.e., have lower scores on the RDoF scoring protocol) than the cross-disciplinary sample.…”
Section: Introductionmentioning
confidence: 99%
“…RRs therefore improve (1) methods by allowing peerreviewers to provide valuable feedback on the study protocol during the crucial planning stages, (2) reporting and dissemination by ensuring that the accepted protocol is followed and results are interpreted appropriately, (3) reproducibility by reducing questionable research practices and requiring open data and/or code, (4) evaluation by mitigating the outmoded emphasis on study results to dissipate publication bias, and (5) incentives by restructuring the publication process to give authors control and rewarding open science practices. RRs also champion replication attempts, which are beginning to become more mainstream in psychological and other sciences but are largely absent within the addiction literature (Heirene 2021). Emerging findings attest to the value of RRs: null findings are approximately five times more likely in RRs relative to regular articles, suggesting that they reduce publication bias and/or QRPs (Allen and Mehler 2019;Scheel et al 2021).…”
Section: Traditional Rrsmentioning
confidence: 99%
“…In their 'manifesto for reproducible science ', Munaf o et al (2017) propose five measures that target these threats with the goal of improving research: (1) methods, (2) reporting and dissemination, (3) reproducibility, (4) evaluation, and (5) incentives. Adoption of open science practices will allow many of these measures to be achieved and calls for their implementation in addiction science are becoming louder (Heirene 2021;Louderback et al 2021;Pennington et al 2021). However, to be successful, academic journals also need to adapt and recentre their focus on scientific rigor rather than the metamorphosis of study results.…”
Section: Reshaping the Publication Process: Addiction Research And Theory Joins Peer Community In Registered Reportsmentioning
confidence: 99%
“…Alternatively, they suggested that the pharmacological effects of morphine might impair an animal's ability to engage in reinforcing social activities in the colony environment (6). The Rat Park papers are now 40 years old, yet ongoing media interest and their legacy in the DOI: https://doi.org/10.31885.jrn.1.2020.1318 field continue to support a high replication value for these experiments (7). As several reviews have noted (1,8), an attempted replication of the studies was reported in 1996 and did not show the same effects (9).…”
Section: Introductionmentioning
confidence: 99%
“…The Rat Park papers are now 40 years old, yet ongoing media interest and their legacy in the DOI: https://doi.org/10.31885.jrn.1.2020.1318 field continue to support a high replication value for these experiments (7). As several reviews have noted (1,8), an attempted replication of the studies was reported in 1996 and did not show the same effects (9). However, it is not clear that further direct replication attempts are desirable as the original studies had several methodological flaws including lost data, animals dying during experiments and confounding variables such as intake modality.…”
Section: Introductionmentioning
confidence: 99%